Stable isotope evidence for mid-Pleistocene paleoenvironmental conditions at the site of Kathu Pan 1 (central interior, South Africa). (20th March 2022) - Mohale, Nyebe E.; Codron, Daryl; Horwitz, Liora K.
Abstract: This study investigates the Mid-Pleistocene paleoenvironment and dietary behaviour of ancient herbivores in the South African central interior, today part of the semi-arid Kalahari savanna. Analyses were undertaken of carbon (δ 13 C) and oxygen (δ 18 O) stable isotopes in tooth enamel carbonate of twelve fossil herbivore species from Layers 4b and 4a, associated with Earlier Stone Age (ESA) and transitional ESA-Middle Stone Age (Fauresmith) industries respectively, at the archaeological site of Kathu Pan 1. The data are compared with other Eearly to Mid-Pleistocene herbivore assemblages located in the central interior, namely Cornelia-Uitzoek, Wonderwerk Cave and the Florisbad Spring. Results indicate that the median δ 13 C values for all ungulate taxa at Kathu were >-4‰, indicating predominantly C4 based diets, although in certain taxa, some individuals included a significant C3 component in their diet. The δ 18 O values of most species at Kathu were relatively low, suggesting a cooler and/or wetter climate. Carbon isotope evidence for C4 dominated habitats at Kathu, but with a larger C3 component amongst grazers than today, resembles the other Early to -Mid-Pleistocene assemblages in the region. Similarly, δ 18 O values for Kathu supplement existing evidence that the region was substantially wetter than in modern times.